Puod kasaysayan at kalinangan ng mga pamayanang maritimo sa Pilipinas - Ubaldo, Lars Raymund C.; ADHIKA ng Pilipinas, Inc.; National Commission on Culture and the Arts (Philippines). ([Quezon City] Adhika ng Pilipinas, Inc. Intramuros, Manila National Commission for Culture and the Arts, 2014)
History and culture of maritime communities in the Philippines; collection of articles.
Gift
Includes bibliographical references.
In Tagalog.
Keywords: Fishing villages -- Philippines; Philippines -- Social conditions; Philippines -- Social life and customs